Liver and Hepatocyte Transplantation: What Can Pigs Contribute? - Li, Xiaoxue; Wang, Ying; Yang, Haiyuan; Dai, Yifan (Frontiers in Immunology, 2022)
About one-fifth of the population suffers from liver diseases in China, meaning that liver disorders are prominent causative factors relating to the Chinese mortality rate. For patients with end-stage liver diseases such as hepatocellular carcinoma or acute liver diseases with life-threatening liver dysfunction, allogeneic liver transplantation is the only life-saving treatment. Hepatocyte transplantation is a promising alternative for patients with acute liver failure or those considered high risk for major surgery, particularly for the bridge-to-transplant period. However, the lack of donors has become a serious global problem. The clinical application of porcine xenogeneic livers and hepatocytes remains a potential solution to alleviate the donor shortage. Pig grafts of xenotransplantation play roles in providing liver support in recipients, together with the occurrence of rejection, thrombocytopenia, and blood coagulation dysfunction. In this review, we present an overview of the development, potential therapeutic impact, and remaining barriers in the clinical application of pig liver and hepatocyte xenotransplantation to humans and non-human primates. Donor pigs with optimized genetic modification combinations and highly effective immunosuppressive regimens should be further explored to improve the outcomes of xenogeneic liver and hepatocyte transplantation.